PELESTARIAN BUDAYA LOKAL MELALUI KEBIASAAN MEMAKAI BAJU PESA’AN DALAM MENUMBUHKAN SIKAP CINTA BUDAYA PADA PESERTA DIDIK SDN KRATON 1 BANGKALAN - Dini Maesaroh; Shilfi Rohmatika; Nilamsari Damayanti Fajrin; Erna Dwi Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The preservation of local culture has become a major challenge in the era of globalization, which causes younger generations to lack understanding of their own cultural identity. This study aims to identify the implementation of the habit of wearing pesa'an clothes at school, examine students' understanding of the meaning and philosophy of pesa'an clothes, and analyze the contribution of this habit to the formation of cultural attitudes. This research employed a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The research subjects included teachers, students, and parents at SDN Kraton 1 Bangkalan. The findings indicate that the activity of wearing pesa'an clothes has been routinely conducted every 24th of the month with very high participation rates and has provided a positive impact on students' cultural appreciation attitudes. However, students' understanding of the symbolic meaning, philosophical values, and historical significance of pesa'an clothes remains low, thus creating a gap between cultural practice and cultural understanding. The main obstacles include economic limitations in providing complete attributes and inconsistency in usage according to cultural standards. This study concludes that the habit of wearing pesa'an clothes is effective in fostering cultural appreciation attitudes, but needs to be strengthened with the integration of educational materials, usage guidelines, and collaborative strategies to enhance understanding and sustainable implementation of local cultural preservation